Trucks - Broekel, Ray. (Chicago : Childrens Press, 1983)
Text and photographs describe truck engines, fuel, bodies, tractor trailers, and the specialized types of trucks used to haul or convey specific merchandise.
Includes index.
2.4
K-3
K-4.
Keywords: Trucks -- Juvenile literature; Trucks; Trucks